Yahoo Web Search

  1. Ad
    related to K
  1. Sort by

  1. f(x) = k - x² ← this is the curve y = 4x - 9 ← this is the line ... us only one point, so only one solution to the equation 4x - 9 = k - x² x² + 4x - 9 - k = 0 x² + 4x - (9 + k) = 0 ...

    4 Answers · Science & Mathematics · 24/09/2015

  2. a[k] = 1/ln(k)^ln(k) a[k+1] = 1/ln(k(1+1/k))^ln(k+1) = 1/( ln(k) + ln(1+1/k))^ln(k+1) = 1/ ( ln(k)^ln(k+1) ( 1+ (ln(1+1/k)/ln(k) )^ln(k+1) a[k]/a[k+1] =ln(k)(1+(ln...

    3 Answers · Science & Mathematics · 18/04/2007

  3. "Solve for k in terms of k" doesn't make sense: k=k is obvious. I...thing and see if we can get a cleaner statement of the relationship between x and k: log(base2)x+log(base2)(x+5)=k log(base2) [x(x+5)] = k {by properties of...

    2 Answers · Science & Mathematics · 19/10/2009

  4. ========= x^2 + k + 6 = kx +3x x^2 -x(k+3) + (k+6) = 0 The equation will have equal ... happens when the discriminant is zero. So, solve (k+3)^2 - 4(k +6) = 0 k^2 + 6k + 9 - 4k - 24 = 0 k^2 + 2k - 15 = 0 (k+5)(k-3...

    2 Answers · Science & Mathematics · 14/10/2012

  5. y = k√x y' = k / 2√x Now if the given line is tangent to y = k√x then the slope of the line equals k / 2√x so k / 2√x = 5 k = 10...

    1 Answers · Education & Reference · 16/02/2010

  6. This only true if K is also a metric space. Otherwise there are counterexamples.... Now to prove the claim: Forward direction: Suppose K is compact and A = (x_n) is a sequence in K. We...

    2 Answers · Science & Mathematics · 16/10/2010

  7. Hello, x³ – (k + 1)x + 2k = 0 = = = = = = = = = = = = = = = = = = = = = = Obviously, if k=0, we obtain... prime and k≠0: Then 2k has four divisors: 1, 2, k and 2k. Rational root theorem induce that if a rational root exists...

    2 Answers · Science & Mathematics · 10/12/2012

  8. k=ideal gas constant k=universal gas constant k=constant proportional k=0.08205 L.atm/mol.K (if you're gonna use liter) or k=82.05ml.atm/mol.K (if you're gonna use ml) k is also be R it ...

    1 Answers · Science & Mathematics · 28/04/2008

  9. ... 6/(k+1) - 1/(k) = 1 ← note: k ≠ 0 or -1 or 6(k) - (k+1) = (k+1)(k) or 6k - k - 1 = k² + k or 0 = k² + k- 6k + k...4*3 ) ] / 2 k = [ 4 ± 2√3 ) ] / 2 k = 2 ± √3 k = { 2 - √3, 2 + √3 } k ~ { 0.2679, 3.7321 }

    3 Answers · Science & Mathematics · 11/09/2010

  10. k = (k+15)/3*(k-1) ==> multiply both sides by 3(k-1) to get rid of fractions 3k(k-1) = k+15 ==> expand the LHS 3k^2-3k = k+15 ==> move everything to the LHS 3k^2-4k-15=0 actually this does...

    3 Answers · Science & Mathematics · 21/07/2007

  1. Ad
    related to K
  1. Try asking your question on Yahoo Answers